JENIS DAN POPULASI LALAT BUAH Bactrocera spp. (DIPTERA : TEPHRITIDAE) BERDASARKAN WAKTU TANGKAP PADA AREAL TANAMAN CABAI MERAH DI KOTA TOMOHON - Jantje H. Manangka; Prof.Dr.Ir. Christina L. Salaki, MS.; Ir. Caroulus S. Rante, MS (Universitas Sam Ratulangi, 2017)
ABSTRACTThis study aims to determine the species and population of fruit flies Bactrocera spp. based on different catch time in red chili area at village of Kakaskasen II, Tomohon Utara Subdistrict, Tomohon City. The design used was Randomized Block Design (RBD) which consisted of three treatment time of catching that is treatment A, time period of catch at06.00-12.00; Treatment B, the catch time period at 12.01-18.00, and treatment C, the catch time period at 19.01-05.00. The type of fruit fly is identified to the species level. The population of fruit flies collected were analyzed by analysis of variance (ANOVA) and if the treatment obtained was significantly different then it would be followed by BNJ test.The results showed that the types of fruit flies caught using steiner type traps with methyl eugenol attractants based on the treatment of catch time during observations 1 to 4 in the chili plant area were seven species, namely Bactrocera dorsalis (Hendel), Bactrocera umbrosa (Fabricius), Bactrocera Papayae Drew & Hancock, Bactrocera synnephes (Hendel), Bactrocera carambolae (Drew & Hancock), Bactrocera Facialis (Coquillet)), and Bactrocera sp. The catch time for the highest number of trapped fruit flies is found at the treatment at 06.00-12.00 and12.01-18.00.Key words: Fruit Fly Types, Methyl Eugenol (Petrogenol), Catch Time